Ethical and legal aspects of using generative artificial intelligence technologies in preparing qualification and scientific papers - V. V. Ivanov; A. Yu. Nesterov; I. P. Yanchenko (Вестник Самарского университета: История, педагогика, филология)
The article is devoted to the issue of using generative AI in the higher education system of the Russian Federation. The relevance of this issue is due to the avalanche-like growth in the use of generation by students and postgraduates in the 2023/24 academic year, the heated discussions that arose in this regard within universities, a series of publications in the media, the lack of development of the legal aspects of the use of generation, the ambiguity of its ethical grounds and consequences. The goal of the authors' collective is to formulate a collective position of teachers of classical humanitarian knowledge, which consists in the inadmissibility of using generative AI in the preparation of qualification and scientific papers. The work examines the regulatory aspects of the use of generation, conducts an experimental study of generative systems popular in the Russian-speaking space, and formulates a fundamental threat to subjectivity at the level of the individual and the collective, arising in connection with the use of generative AI. The general conclusion of the work is the need for careful legal and ethical regulation of the areas and methods of using generative systems in higher education.